Strategies for Achieving Competitive Advantage in Transformative Islamic Education - Al As'adie, Mohammad Faried Wajdie; Hasanah, Siti Nur Hidayatul (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2024)
This study aims to identify and analyze the strategy for creating a competitive advantage in the transformative Islamic education service industry at MAN 1 Jombang. Transformative Islamic education is an educational approach that focuses on developing students' character, morals and spirituality to achieve positive transformation in themselves. As an Islamic education institution, MAN 1 Jombang has adopted this approach and strives to attract prospective and retain existing students. This study used qualitative methods with data collection techniques in the form of interviews, observation and document analysis. The results showed that MAN 1 Jombang had implemented several strategies to create a practical competitive advantage, namely: 1) the establishment of a positive image of the institution, 2) improving the quality of education, 3) promotion through social media, and active involvement with the local community. Competitive advantage focuses on the many students who register and are enrolled and the positive changes students can achieve regarding human resource quality, character, and spirituality.